Eye-tracking monitoring based on PMUT arrays - SUN, Sheng (Institutional Knowledge at Singapore Management University, 2021)
As a common and natural activity of human beings, eye movement has been regarded as an indicator of human physiological and psychological health; eye movement tracking has been applied to a wide range of domains, such as disease diagnostics, drug therapy testing and human-computer interaction. Conventionally, eye movement is captured by three approaches, i.e., recording video using a camera, measuring time-varying Electrooculography (EOG) signals using electrodes, and detecting reflected infrared light using infrared sensor. However, all these techniques incur certain limitations that impede their adoption for practical eye tracking, such as privacy violation, high computation resources, discomfort and strong light reliability. This paper presents a portable and robust eye tracking technique based on ultrasound. Specifically, piezoelectric MEMS ultrasonic transducer arrays integrated on glasses are used to transmit and receive bio-safe pulse echo ultrasound individually. With experiment on volunteers, the developed devices can accurately track the rotation and direction of eyeball movement in real-time, based on the time of flight (TOF) principle. The tracking device is lightweight (